Development of Arabic Writing Skill Web-Based Learning Media Using Baamboozle Website - Satyaningrum, Retnowati; Sholihah, Faizatun; Azis, Abdul Jalil; Wicaksono, Meidias Abror; Machmudah, Umi (Fakultas Bahasa dan Seni UNP, 2025)
The goal of this research is to create learning resources for writing skills (maharah kitabah) using the Baamboozle website. Research and development is the research methodology employed. Researchers employed the development of the ADDIE model which is divided into five phases: analysis, design, development, implementation, and evaluation. In order to evaluate the viability of the generated items, documentation and questionnaires were employed as data collection methods in this Baamboozle media development research. The quantitative descriptive analysis technique was employed in this study. After that, the information gathered from students and learning media specialists via surveys about the created items was examined. Based on the findings from the analysis stage, researchers carried out a needs analysis of Arabic learning media; they also designed this product into two categories: distinct letters and random words; in the development stage, they created materials, had media experts verify their viability, and made revisions to their products. The product was evaluated on 21 students in grade VII as part of the evaluation process, which looks for evidence that the product was designed in accordance with learning objectives. The average result of the three experts' assessment was 87.78%, placing it in the Very Good category. The generated teaching material products received a percentage of 89.89% in the student assessment questionnaire, placing them in the